Redrawing subnational territories as government reform towards a framework for comparative analysis - Tumanut, Michael A. (2015)
Subnational territories are continuously being redrawn in many countries, whether through merger, annexation or fragmentation. Although several theories and models have been studied and proposed, they cannot adequately explain why the rate of territorial reform varies among polities in general, or why, in one country, territorial reform vary, not just temporally, but spatially and in outcome (success or failure). Comparative studies theorizing territorial reform in general are scant and findings inconclusive and disjointed, as discourse among scholars on this topic is limited. The literature is also found biased toward Western reforms and territorial merger. It is for these reasons that this article aims to unify fragmented findings using a modified and consolidated framework anchored on Tsebelis' interpreted veto players theory and Ostrom's institutional analysis and development framework. In institutions or policies, reform is a function of the number of effective veto players and the congruence of their preferences, both of which are shaped by the formal and informal rules.
Keywords: Administrative reform